1970
DOI: 10.3329/jbs.v14i0.457
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Repellant Activity of Three Spice Materials on <i>Tribolium castaneum</i> (Herbst) Adults

Abstract: The chloroform extracts of coriander (Coriandrum sativum L.), ajowain (Trachyspermum ammi (L.) Link.) and fenugreek (Trigonella foenum-grecum L.) were tested against the red flour beetle, Tribolium castaneum (Hbst.) adults through residual film assay and their repellent activity were also conducted. The LD50 values for coriander, ajowain and fenugreek were 316. 173 and 243.5895, 271.4573 and 232.7095, and 159.0106 and 4.194236 µg/cm 2 for 24-and 48 h of exposure respectively. According to the intensity of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…These semio-chemicals probably provided a vapour barrier preventing C. puncticollis from touching tubers surfaces [25]. These observations also correspond with the reports of Tapondjou et al, [26], Ukeh et al, [27], Farhana et al, [28], Ajayi and W intola [29] and Akinkurolere et al, [30] who separately reported that n-hexane or ethanolic extract of D. tripetalla, A. melegueta and X. aethiopica could individually cause 40.1% to 100% repellence when used to protect grains or dry fish from storage coleopterans (beetles).…”
Section: Discussionsupporting
confidence: 89%
“…These semio-chemicals probably provided a vapour barrier preventing C. puncticollis from touching tubers surfaces [25]. These observations also correspond with the reports of Tapondjou et al, [26], Ukeh et al, [27], Farhana et al, [28], Ajayi and W intola [29] and Akinkurolere et al, [30] who separately reported that n-hexane or ethanolic extract of D. tripetalla, A. melegueta and X. aethiopica could individually cause 40.1% to 100% repellence when used to protect grains or dry fish from storage coleopterans (beetles).…”
Section: Discussionsupporting
confidence: 89%
“…Treating wheat grains with coriander oil at different rates (5, 10 and 15%) associated with slight effect on grains on both of (number of infected wheat grains, damage grains percentage and grains weight loss percentage) as compared treating with neem or mustard oils after 3 and 6 month of storage as well combined over storage periods, these results may be due to the essential oil of coriander exhibited good fumigant, repellent and volatile toxicity against larvae and adult insects (Pascual-Villalobos and Ballesta-Acosta, 2003 ;Farhana et al, 2006 ;Islam et al, 2009 andRani, 2012).  Effect of control treatments:…”
Section: Resultsmentioning
confidence: 99%
“…Screening for pesticidal activity was carried out using surface film method [ 22 – 24 ], is a simple and widely used method. The working solution was prepared by dissolving 100 mg experimental sample in 2 ml mixed solvent (50% chloroform + 50% methanol) in a vial.…”
Section: Methodsmentioning
confidence: 99%